Management of Recurrent Venous Thromboembolism in Severe Immune Thrombocytopenia: A Case Report and a Review of the Literature - Nielsen, Mathias Haargaard; Bor, Mustafa Vakur (Hämostaseologie, 2023)
We report a case of a 58-year-old man with recurrent unprovoked deep vein thrombosis (DVT) and severe immune thrombocytopenia (ITP) with a platelet count of 19 × 109/L. We further review studies reporting venous thromboembolism (VTE) in patients with severe ITP (≤ 35 × 109/L) and identified 14 patients highlighting VTE risk factors and management of these patients. The present case had several risk factors for VTE (previous DVT, obesity, heterozygosity for factor V Leiden mutation, and previous splenectomy). The patient was initially treated with low-molecular-weight heparin followed by long-term apixaban treatment. The literature review together with our case demonstrates that VTE in severe ITP (≤ 35 × 109/L) can occur in patients with VTE risk factors and antithrombotic management of these patients can be achieved without bleeding depending on severity of thrombocytopenia either by full or reduced dose of anticoagulation together with ITP therapy.
Keywords: immune thrombocytopenia; venous thromboembolism; thrombotic disorder